Modulation of corticomotor excitability in response to distal focal cooling - Yekta Ansari; Anthony Remaud; François Tremblay (PeerJ, 2018)
Background Thermal stimulation has been proposed as a modality to facilitate motor recovery in neurological populations, such as stroke. Recently (Ansari, Remaud & Tremblay, 2018), we showed that application of cold or warm stimuli distally to a single digit produced a variable and short lasting modulation in corticomotor excitability. Here, our goal was to extend these observations to determine whether an increase in stimulation area could elicit more consistent modulation. Methods Participants (n = 22) consisted of a subset who participated in our initial study. Participants were asked to come for a second testing session where the thermal protocol was repeated but with extending the stimulation area from single-digit (SD) to multi-digits (MD, four fingers, no thumb). As in the first session, skin temperature and motor evoked potentials (MEPs) elicited with transcranial magnetic stimulation were measured at baseline (BL, neutral gel pack at 22 °C), at 1 min during the cooling application (pre-cooled 10 °C gel pack) and 5 and 10 min post-cooling (PC5 and PC10). The analysis combined the data obtained previously with single-SD cooling (Ansari, Remaud & Tremblay, 2018) with those obtained here for MD cooling. Results At BL, participants exhibited comparable measures of resting corticomotor excitability between testing sessions. MD cooling induced similar reductions in skin temperature as those recorded with SD cooling with a peak decline at C1 of respectively, −11.0 and −10.3 °C. For MEPs, the primary analysis revealed no main effect attributable to the stimulation area. A secondary analysis of individual responses to MD cooling revealed that half of the participants exhibited delayed MEP facilitation (11/22), while the other half showed delayed inhibition (10/22); which was sustained in the post-cooling phase. More importantly, a correlation between variations in MEP amplitude recorded during the SD cooling session with those recorded in the second session with MD cooling, revealed a very good degree of correspondence between the two at the individual level. Conclusion These results indicate that increasing the cooling area in the distal hand, while still eliciting variable responses, did produce more sustained modulation in MEP amplitude in the post-cooling phase. Our results also highlight that responses to cooling in terms of either depression or facilitation of corticomotor excitability tend to be fairly consistent in a given individual with repeated applications.